Prognosis of sciatica and back-related leg pain in primary care: the ATLAS cohort - Konstantinou, Kika; Dunn, Kate M.; Ogollah, Reuben O.; Lewis, Martyn; Windt, Danielle van der; Hay, Elaine M. Hay (Elsevier, 2017)
BACKGROUND CONTEXT: Evidence is lacking on the prognosis and prognostic factors of back-related leg pain and sciatica in patients seeing their primary care physicians. This evidence could guide timely appropriate treatment and referral decisions. PURPOSE: The present study aims to describe the prognosis and prognostic factors in primary care patients with low back-related leg pain and sciatica. STUDY DESIGN: This is a prospective cohort study. PATIENT SAMPLE: The present study included adults visiting their family doctor with back-related leg pain in the United Kingdom. OUTCOME MEASURES: Information about pain, function, psychological, and clinical variables, was collected. Good outcome was defined as 30% or more reduction in disability (Roland-Morris Disability Questionnaire). METHODS: Participants completed the questionnaires, underwent clinical assessments, received a magnetic resonance imaging scan, and were followed-up 12 months later. Mixed-effects logistic regression evaluated the prognostic value of six a priori defined variable sets (leg pain duration, pain intensity, neuropathic pain, psychological factors, clinical examination, and imaging variables). A combined model, including variables from all models, examined independent effects. The National Institute for Health Research funded the study. There are no conflicts of interest. RESULTS: A total of 609 patients were included. At 12 months, 55% of patients improved in both the total sample and the sciatica group. For the whole cohort, longer leg pain duration (odds ratio [OR] 0.41; confidence interval [CI] 0.19-0.90), higher identity score (OR 0.70; CI 0.53-0.93), and patient's belief that the problem will last a long time (OR 0.27; CI 0.13-0.57) were the strongest independent prognostic factors negatively associated with improvement. These last two factors were similarly negatively associated with improvement in the sciatica subgroup. CONCLUSIONS: The present study provides new evidence on the prognosis and prognostic factors of back-related leg pain and sciatica in primary care. Just over half of patients improved at 12 months. Patient's belief of recovery timescale and number of other symptoms attributed to the pain are independent prognostic factors. These factors can be used to inform and direct decisions about timing and intensity of available therapeutic options.